Endomyocardial biopsy of patients submitted to heart transplantation: descriptive study and histologic analysis of the specimens - Castro Neto , Josué V.; Carvalho , Alexandre R. de; Contreras , Carlos Mendez; Cipullo , Reginaldo; Finger , Marco Aurélio; Chaccur , Paulo; Zamorano , Mabel; Manrique , Ricardo; Magalhães , Hélio M.; Dinkhuysen, Jarbas Jackson (Brazilian Journal of Transplantation, 2005)
Objective: to describe the technique, complications and histologic alterations of patients submitted to endomyocardial biopsy in the post-operative period of heart transplantation. Methods: we study 232 procedures of right ventricle endomyocardial biopsy of 38 patients operated between January 2000 and December 2002. Exclusion criteria were: in hospital mortality (not submitted to biopsy) and incomplete criteria for protocol. Results: all procedures were done through the right internal jugular vein. The bioptome utilized was a 2,2 x 510 mm- 7Fr. These were done under fluoroscopic guidance. In average we obtain 5,1 pieces by procedure. In 48 (18,1%) procedures no cellular rejection (grade 0) was evidenced. Between rejections, the most common was acute, focal and mild (grade IA)-55%. In the 6 months period after surgery, grade IA was 41,2% and grade IB (diffuse and mild) 32,4%. After 6 months, were 56% and 12,5%, respectively. There were 9 complications (3,8%). The most common was hemopericardium with pericardial drainage (1,3%). Conclusions: Right ventricle endomyocardial biopsy was accomplished with low morbidity. The principal complication was hemopericardium. Avaliation of standardized histologic grading revealed that the principal type was grade IA and that in the 6 months period after surgery it was 41,2% and after 6 months it was 56%.